Pastoral urbana : uma abordagem a partir da obra do teólogia Joseph Comblin - Pereira, Paulo César (2011)
Following a worldly trend, the Brazilian towns have come across great changes in the last fifty years, in which one observe a quick displacement of the rural population toward big urban centers. A lot of them have been turned into real metropolises, bringing out with themselves their virtues and limitations and them they have built a new social tissue, that also has gradually been inserted in the larger post-modernity context. In post-modern cities, the relations distance-proximity and sacred-profane were submitted to changes, leading to new configurations within the religions field, bringing out a clear distinction between religion and religiosity and transforming the full living experience regarding to faith into a big tergiversation through individualization and valorization of subjectivity. The city also arises itself as an space for transition and consume, existing, in this case, a full strategy, in which one seeks to make the distinction among the social classes, placing them into a certain competition and so obstructing that one could arrive to a level of saturation and satisfaction of needs. It is in this context that urban pastoral is inserted, being defined as church s evangelizing mission in the city. In Brazil, one has a centenarian church, with an also centenarian structure, that intends to accomplish that task. In this research, we aimed to problematize the urban pastoral, departing from the point of view of the theologian Joseph Comblin, situating him in post-modernity context, and seeking to accomplish an analysis regarding to the receptivity, by the Catholic Church, of his ideas. We also sought to make more careful reflections regarding to the practices fully lived within the pastoral, analyzed according to Comblin s thought and viewpoint. We used hermeneutics for evaluating that theologian s ecclesiological work, as well as in order to emphasize his life aspects, concerning his life according to interviews conducted with the author. Comblin presents himself as a theologian with a complex thought, and that manifests himself in a cross disciplinary way. He diverges, with certain facility, from the positions adopted by the Church and, since he does not believe in the actual structure, he proposes alternatives for it, so that Church could, departing from a new pastoral model, be more inserted into society and could partake in the changes that unavoidably go on happening in the cities